2020
DOI: 10.3390/nu12020367
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Is Less Frequently Associated with Cognitive Impairment in Elderly Individuals: A Cross-Sectional Study in Yogyakarta, Indonesia

Abstract: Obesity is one of the factors associated with cognitive impairment. However, obesity may differently affect cognitive function in different age groups, and scarce data are available from low- and middle-income countries. This cross-sectional study aimed to identify the association between obesity and cognitive impairment among 143 elderly individuals in Yogyakarta. We recorded the sociodemographic factors and some comorbidities, also measured the body mass index as a parameter of obesity, cognitive function us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 60 publications
5
24
0
Order By: Relevance
“…MoCA-INA is a 30-point cognitive screening tool which has been validated for Indonesia population. It has been widely accepted and commonly used in the clinical and community setting in Indonesia [25,26]. The cut-off point to be assessed as cognitively impaired is <26 [27].…”
Section: Plos Onementioning
confidence: 99%
“…MoCA-INA is a 30-point cognitive screening tool which has been validated for Indonesia population. It has been widely accepted and commonly used in the clinical and community setting in Indonesia [25,26]. The cut-off point to be assessed as cognitively impaired is <26 [27].…”
Section: Plos Onementioning
confidence: 99%
“…However, the association between obesity and cognitive impairment in the elderly is unclear. Several studies have demonstrated that general obesity as classified using body mass index (BMI) was associated with a decreased risk of cognitive impairment in the elderly, while abdominal obesity was harmful to cognitive function (13)(14)(15). In contrast, other studies have reported that both general and abdominal obesity were associated with an increased risk of cognitive dysfunction in old age (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Executive performance plays a key role in regulating behavior, emotion, thought, and, consequently, self-control [13][14]. A significant correlation between high body mass and low cognitive function has been reported, indicating that higher body mass is associated with lower cognitive function [15][16][17]. Cognitive performance is a subset of executive performance that refers to a set of skills and processes related to self-management and the use of one's own cognitive resources to achieve a goal (performing actions to achieve a goal) [16].…”
Section: Introductionmentioning
confidence: 99%
“…A significant correlation between high body mass and low cognitive function has been reported, indicating that higher body mass is associated with lower cognitive function [15][16][17]. Cognitive performance is a subset of executive performance that refers to a set of skills and processes related to self-management and the use of one's own cognitive resources to achieve a goal (performing actions to achieve a goal) [16]. Recent studies on obese people also show dysfunctional performance characteristics in them [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation